Public-Sector Compensation over the Life Cycle - Pedro Maia Gomes; Felix Wellschmied (Institute of Labor Economics (IZA), 2020)
The size of the public sector in terms of employment and compensation has a strong life-cycle dimension. We establish a quantitative partial-equilibrium life-cycle model with incomplete markets, private and public sectors, and risk-averse workers, and use it to (i) calculate three dimensions of public-sector compensation: wage, pension, and job-security premia, and (ii) quantify the effects of harmonizing the compensation in the two sectors. We find that the job-security and pension's premia are important forms of compensation to public-sector workers. Harmonizing the characteristics of public employment with those of the private sector would lower the unemployment rate and reduce government costs.
Keywords: J45; E24; H30; H55; 330; public-sector employment; public-sector wages; life cycle; unemployment; retirement; pensions; job security